2021
DOI: 10.1111/papr.13071
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for chronic pain treatment during the COVID‐19 pandemic: Do pain intensity and anxiousness correlate with patient acceptance?

Abstract: Introduction:Recent recommendations for the treatment of chronic pain patients during the coronavirus disease 2019 (COVID-19) pandemic suggest using telemedicine instead of in-person consultations. Knowing whether patients with chronic pain are receptive to the use of telemedicine during a pandemic might improve tailored care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“… 24 These findings highlight the importance of ensuring that individuals with chronic conditions continue to have stable access to various therapies even amidst public health crises. 64 Utilization of virtual telemedicine can help to improve access for some individuals, 65 , 66 but such online interventions must include evidence-based, multidisciplinary pain management supports 64 and, as highlighted in our analysis, virtual care may not always be a suitable alternative.…”
Section: Discussionmentioning
confidence: 97%
“… 24 These findings highlight the importance of ensuring that individuals with chronic conditions continue to have stable access to various therapies even amidst public health crises. 64 Utilization of virtual telemedicine can help to improve access for some individuals, 65 , 66 but such online interventions must include evidence-based, multidisciplinary pain management supports 64 and, as highlighted in our analysis, virtual care may not always be a suitable alternative.…”
Section: Discussionmentioning
confidence: 97%
“… 58 Another study by Harnik et al found patients’ acceptance of telemedicine during the COVID-19 pandemic was high overall but lower among those with levels of pain and anxiety higher than the mean indicating telemedicine may not suffice for this subgroup. 59 Another recent narrative review detailed best practices for telehealth use and remote physical examinations. 60 Other studies of single provider delivery of telemedicine interventions for chronic pain have found that patients generally find delivery of these interventions via telemedicine acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, pain catastrophising or anxiety was linked to greater perceived severity of pain during the pandemic [78,81]. Although widespread adoption of telemedicine facilitated healthcare access, patients with higher pain burden or level of anxiety were found to be less accepting of telemedicine [82] and patients who also had delays or cancellations of interventions were more likely to report increased pain [83,84]. There was a substantial increase in opioid overdose deaths in the United States and Canada during the pandemic [5,85], but it is not clear if opioid prescriptions to pain patients was contributory.…”
Section: Pandemic Influence On Patients With Pre-existing Chronic Painmentioning
confidence: 99%